Royal College of Physicians Intercollegiate Stroke Working Party evidence‐based guidelines for the secondary prevention of stroke through nutritional or dietary modification. Issue 2 (18th June 2014) - Hookway, C.; Gomes, F.; Weekes, C. E.
Abstract: Background: Each year, 15 million people worldwide and 110 000 people in England have a stroke. Having a stroke increases the risk of having another. There are a number of additional known risk factors that can be modified by diet. The present study aimed to systematically review key nutrients and diets and their role in secondary prevention, as well as provide evidence‐based guidelines for use in clinical practice. The work was conducted as part of the process to develop the 4th edition of the Royal College of Physicians' (RCP) National Clinical Guideline (NCG) for Stroke . Methods: Questions were generated by the research team, in consultation with the Virtual Stroke Group, an online professional interest group, and the RCP Intercollegiate Stroke Working Party Guideline Development Group. Nine questions covering several individual nutrients and diet combinations were defined and searches conducted up until 31 October 2011 using five electronic databases (Embase, Medline, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Cochrane Library and Web of Science). All included studies were assessed for quality and risk of bias using van Tulder criteria for randomised controlled trials (RCTs) and Quality of Reporting of Meta‐analyses (QUORUM) criteria for systematic reviews. Results: Of 4287 abstracts were identified, 79 papers were reviewed and 29 systematic reviews and RCTs were included to provide evidence for the secondary prevention components of the guidelines. For each question, evidence statements, recommendations and practical considerations were developed. Conclusions: This systematic review process has resulted in the development of evidence‐based guidelines for use in clinical practice and has identified areas for further research.